Peripartum cardiomyopathy. (7th September 2021) - Kulkarni, Akshatha; Squire, Gareth; Hogrefe, Kai; Waseem Osman, Mohamed
Abstract : Key content: The increasing incidence of peripartum cardiomyopathy (PPCM) is associated with advancing maternal age, multiple gestation, obesity and increasing awareness of the implications of the disease. A 'two‐hit' model of pathogenesis has been proposed, wherein a vascular insult secondary to hormonal effects of advanced pregnancy prompt cardiomyopathy changes in women with underlying genetic predisposition. The emphasis should be on making a diagnosis, and not simply excluding a diagnosis. Early involvement of a multidisciplinary team and senior clinicians is imperative in managing these women effectively. Newer pharmacotherapeutic agents to treat PPCM lack adequate evidence, making their use experimental. Learning objectives: To understand the principles of clinical assessment, which sometimes mimic physiological symptoms of pregnancy. To understand how to manage women with PPCM in a multidisciplinary setting and become familiar with the various pharmacotherapies available. To understand the importance of counselling women on long‐term prognosis and implications on future pregnancy. Ethical issues: The unexpected presentation of the disease and the acuity of illness profoundly affects women at an early stage of their lives. Sparse knowledge means there is uncertainty on the long‐term prognosis, which poses a challenge in counselling for future pregnancies.